Crosshairs: a detective Michael Bennett thriller (Detective Michael Bennett thriller, 16,, 2024)
"Detective Michael Bennett faces a professional sniper who could be anyone--anywhere--in New York City. A killer uses fearsome precision to take out impossible targets. Bennett teams up with a shooting expert--a former Army Ranger and sniper with the NYPD's Emergency Services Unit. But Officer Rob Trilling seems more comfortable with rifles than he is with people. When his new partner begins to log unexplained absences from duty, only Bennett can prove whether the decorated officer is a lonely hunter or a hardened assassin"--